Deteksi Spatial Dependence terhadap Fixed Effects Model Prevalensi Stunting - Asih Murwiati (Jurnal Ekonomi Pembangunan, 2021)
Stunting is one of the three things that affect the growth of children and, more broadly, is an indicator of malnutrition problems. The indicators of chronic nutritional deficiencies are children who are underdeveloped, stunted and underweight. Some children in Indonesia who are under 5 years of age are stunted. This figure puts Indonesia as a country that has a high prevalence of stunting according to the World Health Organization (WHO) classification. Every country has a different character of society and different policies and different approaches. Likewise with Indonesia, there are different variations in terms of demographics, economics and socio-culture. Spatial analysis is one of the analytical tools in capturing regional characteristics. This study uses panel data sourced from the Indonesian Central Bureau of Statistics (BPS) from all provinces during the 2015-2018 period. The test results show that there is spatial dependence, and the spatial error model can be an alternative in choosing a spatial model.